A DEMAND ANALYSIS FOR CEMENT IN NIGERIA (1970)
This study was motivated by the fact that although there are several works on the supply of cement in Nigeria, the demand aspect has not been examined in detail and quantitatively. This study attempts to estimate the price and income elasticities of demand for both imported cement and for aggregate demand for cement in Nigeria. It also attempts to assess the impact of custom tariff on imported cement and appraise the import substitution effects of the domestic manufacturing of cement in Nigeria. And finally, the thesis attempts to show the trend of cement consumption in Nigeria between 1948 - 66, the annual rate of growth of consumption during this period as well as the future time path of this rate of growth. The market analysis in chapter two deals with the supply and demand determinants and the pricing policies of the firms. The market structure is also analyzed and the results of the carefully managed government foreign policy in respect of importation of cement. An appropriate model is postulated in chapter three to grapple with the problem of the demand equations. The theoretical framework is also discussed in this chapter. Chapter four is devoted to the discussion of the results of the estimated demand equations. The least squares method is used to estimate the parameters of the equations. Prom the results it is concluded that cement is price inelastic; both aggregate and imported cement exhibit low and shifting price elasticity. Aggregate demand for cement is "income" elastic. The income elasticity for imported cement is however low, this is a sign of increasing import substitution. The impact of tariff on imported cement is somewhat low when measured in terms of elasticity. The trend of cement consumption during the reference period shows that cement consumption has been growing at a decreasing rate. The rate of growth tends to about 2% with time though the level of consumption grows infinitely large with time.